PENGARUH BEBAN KERJA DAN TANGGUNG JAWAB TERHADAP STRESS KERJA ANGGOTA KEPOLISIAN - Deva Alina Saputri; Yasmine Wafa Wardani, Diana Ayu Lestari, Ratu Dwinov Putri, Tugimin Supriyadi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The Republic of Indonesia Police is one of the agencies that utilizes human resources. The role of human resources is very much needed in the institutional development process. The police agency operates in the military sector, namely defense and state security, so it requires quite large human resources. As members of the police, they have a large workload and responsibility in carrying out their duties. Excessive workload can have negative impacts such as low quality of work, physical fatigue, and decreased concentration. Factors that influence workload are divided into external and internal factors. Apart from the workload, police officers also have the responsibility to carry out their duties by using the power of action or discretion selectively and proportionally so that they can be legally accountable. High workload and responsibility can cause work stress which affects the performance of police officers. This research aims to analyze the factors that influence police workload and responsibilities and their impact on work stress and performance using a literature review method from 7 related national research journals